PENGARUH KOMUNIKASI DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI HOTEL BOROBUDUR JAKARTA - Al Agus Kristiadi; Diah Pratiwi (Human Capital Development, 2018)
Purpose- This study aim is to determine the communication and compensation effect partially or simultaneously to work productivity at Borobudur Jakarta hotel. Design/methology/approach-The population in this study are employees at Borobudur Jakarta Hotel. the samples used in this study as many as 105 people. The sampling technique used wasnon probability sampling. Methods of data analysis used in this study is to test the validity, reliability test, classic assumption test (normality test, multicollinearity, heteroscedasticity test and linearity test). While testing the hypothesis includes the F-test, t test and partial correlation analysis and the coefficient of determination (R²). Findings-From the analysis it can be seen that communication variable, direct compensation variable, indirect compensationvariable has an influence on the work productivity either partially or simultaneously.